Copyright laws and information technology usage as factors influencing information services delivery in university libraries in Edo State, Nigeria - Adenekan, Tolulope E.; Okuonghae, Nosakhare (Folia Toruniensia, 2023)
The study examined copyright laws and information technology usage as factors influencing information services delivery in universities in Edo State. The research design employed was a descriptive survey. The population comprised 43 respondents. Considering the controllable size of the population, the total enumeration sampling technique was adopted. The instrument for data collection was a self-structured questionnaire, which was converted to a google online questionnaire form. It was administered to the respondents via the WhatsApp platforms. The data collected were analysed using descriptive statistics. The finding from the study revealed that copyright laws have a significant effect on information service delivery in these institutions. Similarly, it was also revealed that the use of information technology by library staff in information service delivery in universities libraries in Edo State is very high. The study also include recommendations and its limitations.